REVIEW OF PRACTICE AND POSSIBLE DIRECTIONS OF CONCRETIZATION THE PROGRAM OF STATE GUARANTEES FОR FREE MEDICAL CARE FOR RUSSIAN CITIZENS - D. V. Fedyaev; L. S. Melnikova; V. I. Ignatyeva (IRBIS LLC, 2017)
The article describes questions about State Guarantees fоr free Medical care for Russian Citizen, how they are reflected in existing Programs and changing in the annual revision. Proposed the basic directions of concretization and specified criteria for certain types of medical care. Estimate the positive and negative sides of the proposed reforms.